'Silent Revolution': The Transformation of the Québécois Identity. (15th December 2017) - Létourneau, Jocelyn
Abstract : Since the early 2000s, the people of Québec appear to have been engaged in the transition or perhaps even the transformation of their collective identity. This is not to suggest that the Québécois now define and present themselves in an entirely new way, but that, steeped in two different fundamental realities – generational change and the place held by immigrants in modern Québec – they are open to new answers to the three questions that have continually echoed through their self-reflections as a collective subject of and in history: Where did we come from? Who are we? Where are we going? As a result, Québec – or so this article submits – is in transition. It is somewhere between the tree of its past and the bark of its future, hesitating to choose between the known impossibilities of the past and the unknown possibilities of the future. Québec is facing options that each person, based on their own perspective, views with hope or dread.